2017
DOI: 10.1371/journal.pone.0184029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of infection spread by co-transmitted defective interfering particles

Abstract: Although virus release from host cells and tissues propels the spread of many infectious diseases, most virus particles are not infectious; many are defective, lacking essential genetic information needed for replication. When defective and viable particles enter the same cell, the defective particles can multiply while interfering with viable particle production. Defective interfering particles (DIPs) occur in nature, but their role in disease pathogenesis and spread is not known. Here, we engineered an RNA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
0
31
1
Order By: Relevance
“…Interestingly, the speed of IPs spread at the front remained constant even when the front difference of DIPs and IPs was very small (see Figure 3(g), (h) and Figure 5(c), (d)). This provides a good contrast with a previous study which has demonstrated a considerable delay in the spread of infectious particles (Baltes et al, 2017),…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, the speed of IPs spread at the front remained constant even when the front difference of DIPs and IPs was very small (see Figure 3(g), (h) and Figure 5(c), (d)). This provides a good contrast with a previous study which has demonstrated a considerable delay in the spread of infectious particles (Baltes et al, 2017),…”
Section: Discussioncontrasting
confidence: 83%
“…These particles have shown a substantial decrease in the virus growth without any direct interaction to the wild-type viruses, i.e. IPs, (Baltes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we cannot guarantee that a fast-growing virus will suppress growth of a slow-growing virus, then this strategy might be risky. For example, some have suggested using defective interfering particles (DIPs) as a possible method for blocking infections [51][52][53][54][55]. DIPs cannot replicate on their own, but have a high growth rate when fully-functioning virus is present.…”
Section: Discussionmentioning
confidence: 99%
“…5), and it is expected that also in DIP-virus system, there is a tendency to self-organize so that the 445 intact virus take over the front. It is worth mentioning that experiment on the spreading of DIPs and viruses mixture in space reported highly heterogeneous pattern in some conditions [43], demonstrating the importance of stochastic-ity. It is an interesting future work to extend the model to include stochastic population fluctuations in pirate-helper phage system, as well as analyzing it…”
mentioning
confidence: 97%